Over-representation of the G12S polymorphism of the SDHD gene in patients with MEN2A syndrome (Clinics, 2012)
OBJECTIVE: To evaluate whether germline variants of the succinate dehydrogenase genes might be phenotypic modifiers in patients with multiple endocrine neoplasia type 2. Mutations of genes encoding subunits of the succinate dehydrogenase are associated with hereditary paraganglioma/pheochromocytoma syndrome. Pheochromocytoma is one of the main manifestations of multiple endocrine neoplasia type 2 caused by germline mutation of the rearranged during transfection proto-oncogene. METHODS: Polymorphisms of the succinate dehydrogenase genes were analyzed in 77 rearranged during transfection mutation carriers, 47 patients with sporadic medullary thyroid cancer, 48 patients with sporadic Pheo, and 100 healthy individuals. Exons 10-16 of the rearranged during transfection proto-oncogene were analyzed by direct DNA sequencing, and all exons of the von Hippel-Lindau, succinate dehydrogenase B, and succinate dehydrogenase subunit D genes were tested by direct DNA sequencing and multiple ligation probe analysis. The G12S polymorphism of the succinate dehydrogenase subunit D gene was determined by restriction fragment length polymorphism. RESULTS: Of the 77 rearranged during transfection mutation carriers, 55 from 16 families had multiple endocrine neoplasia type 2A, three from three families had multiple endocrine neoplasia type 2B, and 19 from two families had familial medullary thyroid carcinoma. Eight of 55 (14.5%) patients with multiple endocrine neoplasia type 2A had this variant whereas it was absent in multiple endocrine neoplasia type 2B, familial medullary thyroid carcinoma, sporadic medullary thyroid carcinoma, and sporadic pheochromocytoma groups, and its prevalence in controls was 1% (p<0.002 multiple endocrine neoplasia type 2A versus controls). No associations between G12S and age of manifestation, incidence of pheochromocytoma or hyperparathyroidism, or level of serum calcitonin were observed. CONCLUSION: The high prevalence of the G12S variant in patients with multiple endocrine neoplasia type 2A raises questions about its role as a genetic modifier, but this proposal remains to be established.